Modern student youth civic identity: political activity or social responsibility? - Khairullina, Elmira R.; Shubovich, Marina M.; Bogdanova, Venera I.; Slepneva, Elena V.; Mashkin, Nikolay A.; Rodyukova, Tatiana N. (Opción, 2020)
The purpose of the study is to study the features of the manifestation of civil identity through the perception of political reality and political activity. As a research method, the survey method was used, which allows the most effective consideration of such a structural component of civil identity as the perception of political reality and one’s political activity. As a result, the majority of modern youth has a low political education. In conclusion, in addition to the state Supreme power, the Russian Orthodox Church and the Institute of oligarchy had the same serious powers in Russia.